2019
DOI: 10.1186/s41476-019-0101-8
|View full text |Cite
|
Sign up to set email alerts
|

Spectral composition of low-coherence interferograms at high numerical apertures

Abstract: Interference signals in coherence scanning interferometry at high numerical apertures and narrow bandwidth illumination are spectrally broadened. This enables phase analysis within a spectral range much wider than the spectral distribution of the light emitted by the light source. Consequently, different surface features can be resolved depending on the wavelength used for phase analysis of the interference signals. In addition, the surface topography itself affects the spectral composition of interference sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…The lower heigth value in the microsphere measurement can be attributed to the large influence of the evaluation wavelength on the phase evaluation result and the low-pass filtering transfer characteristic of the entire imaging system. In [10,12] investigations are shown which illustrate the direct relationship between the evaluation wavelength and the measured structure height.…”
Section: Measurement Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower heigth value in the microsphere measurement can be attributed to the large influence of the evaluation wavelength on the phase evaluation result and the low-pass filtering transfer characteristic of the entire imaging system. In [10,12] investigations are shown which illustrate the direct relationship between the evaluation wavelength and the measured structure height.…”
Section: Measurement Resultsmentioning
confidence: 99%
“…Then topographies are calculated from the measurement data using envelope and phase evaluation [24]. It has been shown that the parameters of the phase evaluation are crucial when evaluating the measurement data [10,12].…”
Section: Measurement Resultsmentioning
confidence: 99%
“…One main application of the local spectroscopy technique is to be able to study different materials on the same sample and in the same field of view. With this in mind, we developed a sample consisting of four different materials with the surfaces roughly in the same plane [ 19,20 ] that can be measured locally using the proposed technique as well as with a classical spectrometer with a larger spot size.…”
Section: Spatially (Xyz) Resolved Local Spectroscopy Sing Interference Microscopymentioning
confidence: 99%
“…Failure to reduce the angle of the illumination cone results in degraded spectral measurements as their amplitude is severely attenuated. [ 18,20 ] Because of the need to close down the AD, the lateral measurement spot size is increased to 0.85 μm in diameter. These experimental results demonstrate that depth‐resolved reflectance spectra of buried materials can be performed with interference microscopy.…”
Section: Spatially (Xyz) Resolved Local Spectroscopy Sing Interference Microscopymentioning
confidence: 99%
“…These methods take advantage of the rate of change of interference phase with wavelength to measure a wide variety of objects, including high steps and rough textures. A known difficulty with these techniques is that the transfer characteristics of the optics are wavelength dependent [33,34]. Differences in the spatial frequency response with wavelength can result in large errors in the measured topography, particularly with steep slopes and sharp step-like features.…”
Section:  mentioning
confidence: 99%